Understanding the molecular basis of disease resistance against Septoria Tritici Blotch in wheat - Stephens, Christopher (2022)
Zymoseptoria tritici, a fungal pathogen of wheat and the causal agent of Septoria Tritici Blotch (STB), is a particular challenge to wheat production on a global level, causing crop losses of up to 50% in some cases. Genetic resistance presents an effective way of controlling STB in wheat, with numerous resistance loci having been identified. Stb6, which encodes a wall-associated kinase-like protein and confers resistance to Z. tritici isolates expressing the corresponding AvrStb6 effector, has recently been cloned. However, many questions regarding Stb6-mediated resistance remain unanswered. The global frequency of avirulence AvrStb6 alleles in modern Z. tritici populations remains unknown. The role that AvrStb6 plays in Z. tritici pathogenicity, the nature of its interaction with Stb6 and the mechanism by which Stb6 confers resistance are also yet to be elucidated.